Acrosin inhibitor detection along the boar epididymis - Maňásková-Postlerová, Pavla; Cozlová, Nina; Dorosh, Andriy; Šulc, Miroslav; Guyonnet, Benoit; Jonáková, Věra (International journal of biological macromolecules, 2016)
Epididymal sperm maturation represents a key step in the reproduction process. Spermatozoa are exposed to epididymal fluid components representing the natural environment essential for their post-testicular maturation. Changes in sperm membrane proteins are influenced by proteolytic, glycosylation and deglycosylation enzymes present in the epididymal fluid. Accordingly, the occurrence of inhibitors of these enzymes in the epididymis is very important for the regulation of sperm membrane protein processing. In the present study, we monitored acrosin inhibitor distribution in boar epididymal fluid and in spermatozoa from different segments of the organ. Using specific polyclonal antibody we registered increasing signal of the acrosin inhibitor (AI) from caput to cauda epididymis. Mass spectroscopy examination of the immunoprecipitated acrosin inhibitor (12 kDa) unequivocally identified sperm-associated acrosin inhibitor (SAAI) in the epididymal tissue. Lectin staining showed N-glycosylation in AI from boar epididymis. Protein detection of AI was supported by the results of semi-quantitative RT-PCR showing the presence of mRNA specifically coding for SAAI and similarly increasing throughout the epididymal duct, from its proximal to distal part. Additionally, the immunofluorescence technique showed the AI localization in the secretory tissue of caput, corpus and cauda epididymis, and in the acrosome region and midpiece of the sperm.
Keywords: sekvenční seřazení; transport proteinů; exprese genu; spermie; Mass Spectrometry; Acrosin; Gene Expression; Proteolysis; Protein Transport; Acrosin inhibitor; Molecular Sequence Data; molekulární sekvence - údaje; zvířata; proteolýza; Swine; Amino Acid Sequence; Epididymis; glykosylace; Male; Sequence Alignment; akrosin; epididymis; inhibitory enzymů; Spermatozoa; Animals; Boar epididymis; mužské pohlaví; Glycosylation; hmotnostní spektrometrie; Enzyme Inhibitors; prasata; sekvence aminokyselin